2017
DOI: 10.1002/anie.201700570
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plasma Membrane Ceramides by Super‐Resolution Microscopy

Abstract: The sphingolipid ceramide regulates cellular processes such as differentiation, proliferation, growth arrest and apoptosis. Ceramide-rich membrane areas promote structural changes within the plasma membrane which segregates membrane receptors and affect membrane curvature and vesicle formation, fusion and trafficking. Here, we label ceramides by immunocytochemistry and visualize their distribution on the plasma membrane of different cells with virtually molecular resolution by direct stochastic optical reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

6
3

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 47 publications
(80 reference statements)
1
47
0
Order By: Relevance
“…2, C and D). Recently, ceramiderich membrane areas in the plasma membrane were shown to form pores (54). This, together with our novel data with ceramide labeling, suggests that FTY720 exposure induces the formation of membrane pores, which are enriched in endogenously generated ceramides, altering plasma membrane integrity and inducing necrotic cell death.…”
Section: Fty720 Induces the Formation Of Ceramide-enriched Membrane Psupporting
confidence: 64%
“…2, C and D). Recently, ceramiderich membrane areas in the plasma membrane were shown to form pores (54). This, together with our novel data with ceramide labeling, suggests that FTY720 exposure induces the formation of membrane pores, which are enriched in endogenously generated ceramides, altering plasma membrane integrity and inducing necrotic cell death.…”
Section: Fty720 Induces the Formation Of Ceramide-enriched Membrane Psupporting
confidence: 64%
“…While it is not understood how ceramide may contribute to the inward budding of vesicles at the MVE, facilitating or inducing membrane curvature may be one of its tasks (for biophysical properties of ceramide in membrane curvature, see (Burgert et al, 2017; Goni & Alonso, 2006; Goni, Contreras, Montes, Sot, & Alonso, 2005; Pinto, Silva, Futerman, & Prieto, 2011; L. C. Silva et al, 2012).…”
Section: The Incredible Journey Of a Lipid: Rafting The Extracellularmentioning
confidence: 99%
“…1B). Most recently, research in our and our collaborators’ laboratories has shown that ceramide-rich platforms (CRPs) are 50–200 nm in size and contain ≥ 20 ceramide molecules (Burgert et al, 2017). CRPs are formed when sphingomyelinases convert sphingomyelin into ceramide (Fig.…”
Section: The Incredible Journey Of a Lipid: Rafting The Extracellularmentioning
confidence: 99%
“…Ceramide-rich membrane areas promote structural changes within the plasma membrane, which segregate membrane receptors and affect the membrane curvature and vesicle formation, fusion and trafficking. 19,20 We selected ω-N3-C6-ceramide, which is efficiently incorporated into cellular membranes and can be click-labeled with DBCO-functionalized dyes for fluorescence imaging 21,22 , for further functionalization with a primary amino group (Supporting Information and Supplementary Figures S1-S13). Therefore, we synthesized α-NH2-ω-N3-C6-ceramide from (tert-butoxycarbonyl)-Llysine ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%